Medication adherence inhibitors and facilitators in type 2 diabetic patients: An Integrative review - Fazel Dehvan; Vajiheh Baghi; Asrin Lotfi; Reza Ghanei Gheshlagh (Kurdistan University of Medical Sciences, 2017)
Background & Aim: Diabetes can not be treated, but it can be controlled by treatment regimens. Failure to adhere to therapeutic regimens leads to rapid onset of diabetes complications and undesirable metabolic control and poor clinical outcomes. The objective of this study was to assess the status of medication adherence in patients with type 2 diabetes. Materials & Methods: In this integrated review, all Persian and English articles with full text (from 2000 onwards) were reviewed for  medication adherence in type II diabetic patients. These studies are available from the national and international databases SID, Magiran and Science Direct, PubMed, Google Scholar, Scopus with the keywords "compliance", "concordance" and "adherence" and finally, 53 articles were included in the study. Results: A review of 53 related articles showed that depression, financial problems, adverse drug reactions and illness, memory problems, multiple drug use and complexity of the diet were among the most important inhibitors of adherence to the diet of diabetic patients. Belief in the necessity of medications and patient support were also among the most facilitators of adherence to treatment. Conclusion: Considering the importance of medication adherence in patients with type 2 diabetes and high prevalence of non compliance with treatment, patients should be trained in this field and measures should be taken to remove medication adherence inhibitors .